Cover Picture: Platinum Complexes of a Borane‐Appended Analogue of 1, 1′‐Bis(diphenylphosphino)ferrocene: Flexible Borane Coordination Modes and in situ Vinylborane Formation (Chem. Eur. J. 51/2014). Issue 51 (15th December 2014) - Cowie, Bradley E.; Emslie, David J. H.
<x xml:space="preserve">Abstract</x> An arylborane‐appended analogue of the catalytically important dppf ligand, FcPPB, was prepared and is represented by the industrial robot in the image. FcPPB provided access to platinum complexes featuring η3BCC‐, η2BC‐, η1B‐ and Pt–H–B coordination modes, and reaction of the η3BCC‐coordinated complex with PhC2H transformed the arylborane into an η3BCC‐coordinated vinylborane. For details, see the Full Paper by B. E. Cowie and D. J. H. Emslie on pp. 16899 ff. (FcBBB=1′‐(ortho‐diphenylborylphenyl)‐tert‐butylphosphino‐1‐diphenylphosphinoferrocene)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>